2007
DOI: 10.3389/neuro.03.002.2007
|View full text |Cite
|
Sign up to set email alerts
|

Computational reconstruction of pacemaking and intrinsic electroresponsiveness in cerebellar golgi cells

Abstract: The Golgi cells have been recently shown to beat regularly in vitro (Forti et al., 2006. J. Physiol. 574, 711-729). Four main currents were shown to be involved, namely a persistent sodium current (I Na-p ), an h current (I h ), an SK-type calcium-dependent potassium current (I K-AHP ), and a slow M-like potassium current (I K-slow ). These ionic currents could take part, together with others, also to different aspects of neuronal excitability like responses to depolarizing and hyperpolarizing current injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
177
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(184 citation statements)
references
References 58 publications
3
177
0
Order By: Relevance
“…Model details are already reported in a previous study [13]. We used the biophysical neuron models of a detailed multi-compartmental granule cell [4] and cerebellar Golgi cell [16][17] to generate a large scale detailed network of granular layer that reconstructed center-surround excitation patterns. Our aim was to understand the best parallelization approach for large-scale biophysically detailed neuron circuit models.…”
Section: Introductionmentioning
confidence: 99%
“…Model details are already reported in a previous study [13]. We used the biophysical neuron models of a detailed multi-compartmental granule cell [4] and cerebellar Golgi cell [16][17] to generate a large scale detailed network of granular layer that reconstructed center-surround excitation patterns. Our aim was to understand the best parallelization approach for large-scale biophysically detailed neuron circuit models.…”
Section: Introductionmentioning
confidence: 99%
“…The Golgi cell firing frequency is linearly related to the intensity of their depolarizing drive and a detailed electrophysiological analysis of the Golgi cell active conductances in vitro, coupled to modeling, suggested that I h /I Na-p /I K-AHP / I K-slow can interact to generate slow pacemaking (Forti 2006;Solinas et al 2007a). The same approach revealed that the phase of the regular Golgi cell firing can be reset by spikes evoked by phasic inputs (Solinas et al 2007b; Kanichay and Silver 2008), as observed in vivo.…”
Section: Gap-junctional Coupling Of Firing Golgi Cells Generates Betamentioning
confidence: 99%
“…The biophysical model consisting of cerebellar Golgi neuron consisted of a soma, 3 dendrites and an axon with ion channels mechanisms was used [11] . Synaptic information processing was modelled through AMPA, NMDA and GABA receptor mechanisms implemented as described in [12] .…”
Section: Single Neuron and Synapse Modelsmentioning
confidence: 99%
“…Electrophysiological recordings have been translated to detailed biophysical models of neuronal cells [10,11] to develop biologically realistic mathematical models of microcircuit and to study the molecular and cellular mechanisms underlying cerebellar function [12] . Reconstructions also assist in elaborating animal models for the study of several neurological disorders [9] .…”
Section: Introductionmentioning
confidence: 99%